2010
DOI: 10.1149/1.3374662
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nanostructure in the Electrochemical Oxidation of Model-Carbon Materials in Acidic Environments

Abstract: Carbon is ubiquitous in electrochemical energy devices and may exist in varied forms ranging from crystalline or amorphous to novel nanostructures based on a few sheets of graphene. The electrochemical oxidation of carbon results in the performance degradation of the electrochemical device. A study on the structure-reactivity relationship of the electrochemical oxidation of graphene-based carbon materials ͑carbon black, carbon onions, multiwalled nanotubes, and exfoliated graphite platelets͒ is presented. High… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…At a potential of 0.55-0.60 V (vs. RHE) in the CVs of CB (Figure 8c), there was a redox couple, which was attributed to the redox of quinone/hydroquinone [27]. Gallagher et al [28] also showed the similar CVs, which have redox peaks around 0.6 V, in the case of Vulcan XC72. On the other hand, the CVs of CNSs (Figure 8b) showed no clear redox peaks or an increase in overall capacitance.…”
Section: Corrosion-tolerance Of Support Carbonsmentioning
confidence: 70%
“…At a potential of 0.55-0.60 V (vs. RHE) in the CVs of CB (Figure 8c), there was a redox couple, which was attributed to the redox of quinone/hydroquinone [27]. Gallagher et al [28] also showed the similar CVs, which have redox peaks around 0.6 V, in the case of Vulcan XC72. On the other hand, the CVs of CNSs (Figure 8b) showed no clear redox peaks or an increase in overall capacitance.…”
Section: Corrosion-tolerance Of Support Carbonsmentioning
confidence: 70%
“…However, the post heat-treating in air atmosphere increased the wettability of carbon with the electrolyte of KOH aqueous solution, and the capacitances of electrodes were also enhanced. Furthermore, defects on surface of carbon were proposed to interact with the solvation shells of the ions, decreasing the average carbon surface-ion separation distance, and thereby increasing specific capacitance [20,106]. In Ref.…”
Section: Carbon Surface Structure and Wettingmentioning
confidence: 99%
“…Various studies comparing the electro-oxidation behavior of different carbon materials have been published [16][17][18][19][20]. However, little is unambiguously known regarding the mechanism of electrochemical oxidation [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, few strategies to improve the carbon electro-oxidation resistance have been proposed. Most approaches involve a decrease in the amount of active sites by controlling the carbon morphology and structure [15][16][17][18][19][20]26,27], and/or by reducing the surface area [19,28].…”
Section: Introductionmentioning
confidence: 99%